Pelatihan Manajemen Bengkel Bidang Teknologi dan Rekayasa Bagi Guru Sekolah Menengah Kejuruan (SMK) Canda Bhirawa Pare Kabupaten Kediri - Yoto Yoto; Marsono Marsono; Agus Suyetno; Putri Ardista Nursisda Mawangi; Djoko Kustono (CV. IRA PUBLISHING, 2023)
A workshop at a vocational school is vulnerable to the danger of accidents, especially at technology and engineering vocational schools, therefore the workshop must be managed by professional teachers who have adequate workshop management skills. Therefore, training for vocational school teachers regarding workshop management is very necessary to prevent work accidents for students during activities in the workshop. Training is currently being carried out among 41 productive teachers in the field of technology and engineering at SMK Canda Bhirawa Pare, Kediri. The training was carried out by the LP2M Community Service Team, State University of Malang. Workshop management training is carried out using theoretical and practical material. The training results show that the average competency score for the pre-test is 68.07; post-test score 90.64. So there was an increase in competency from before training compared to after training by 22.57.